1977
DOI: 10.1002/neu.480080404
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of proteins transported at different rates by axoplasmic flow in the dorsal root afferents of rats

Abstract: Proteins synthesized by soma located in L4 dorsal root ganglia and supplied to the axonal branches extending centrally in the dorsal root and peripherally towards the sciatic nerve were analyzed for radioactivity following injections of [3H] leucine into the L4 dorsal root ganglia. All proteins located in the dorsal root and sciatic nerve were analyzed by SDS acrylamide gel electrophoresis at various times post injection. The differences in radioactivity between the dorsal root and sciatic nerve proteins were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

1978
1978
1984
1984

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…The finding of qualitative similarities in FTP synthesized by either retinal ganglion or dorsal root ganglion cells found in this study is in close agreement with previous work showing striking similarities in the FTP found in peripheral motor and sensory axons (Barker, Neale, and Gainer, 1976;Bisby, 1977;White and White, 1977) even when highly sensitive two dimensional gel electrophoretic techniques were used (Stone and Wilson, 1979). This suggests that the major FTP play a common role in the normal maintenance of axons and are not specific to the particular physiological function of that neuron (i.e.…”
Section: Discussionsupporting
confidence: 93%
“…The finding of qualitative similarities in FTP synthesized by either retinal ganglion or dorsal root ganglion cells found in this study is in close agreement with previous work showing striking similarities in the FTP found in peripheral motor and sensory axons (Barker, Neale, and Gainer, 1976;Bisby, 1977;White and White, 1977) even when highly sensitive two dimensional gel electrophoretic techniques were used (Stone and Wilson, 1979). This suggests that the major FTP play a common role in the normal maintenance of axons and are not specific to the particular physiological function of that neuron (i.e.…”
Section: Discussionsupporting
confidence: 93%
“…The absence of major differences corresponding to tract-specific transported proteins has also been reported for the bifurcating neurons of the dorsal root ganglion (Barker et al, 1976;1977;Bisby, 1977;White and White, 1977;Stone et al, 1978) and for retinal ganglion cells which bifurcate to the lateral geniculate and superior colliculus (Siege1 and McClure, 1976;Wagner et al, 1979). However, in each bifurcated neuron, the transmitter of the nerve endings is probably the same.…”
Section: Comparison Of 35s-labeied Proteinsmentioning
confidence: 75%
“…Axonal transport of proteins has been studied extensively in the long, well-defined nerves of the peripheral nervous system (PNS) (Barker et al, 1976;1977;Bisby, 1977;White and White, 1977;Theiler and McClure, 1977;1978;Stone et al, 1978). In the central nervous system (CNS), the optic pathway is also well suited anatomically for such investigations, and the protein classes trans-ported to the optic relay nuclei after injection of radioactive precursor into the vitreous chamber of the eye have been defined in terms of molecular weight distributions and transport rates (Karlsson and Sjostrand, 1971;Marko et al, 1971;Willard et al, 1974;Siege1 and McClure, 1975;Willard and Hulebak, 1977;Wagner et al, 1979).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The polypeptides of axons and synaptic specializations are synthesized in the neuron cell body and carried to their site of utilization by axonal transport (recently reviewed in Grafstein and Forman, 1980;Schwartz, 1979;Wilson and Stone, 1979). Gel electrophoresis techniques have been used to study the population of rapidly transported axonal proteins from the frog (Abe et al, 1974; Barker et al, 1976;1977;Stone et al, 1978;Stone and Wilson, 1979), the rat (Theiler et al, 1976;Bisby, 1977;1980;Theiler and McClure, 1977;; White and White, 1977), and other species (Willard et al, 1974; Barker et al, 1975;Cancalon et al, 1976;Theiler et al, 1976;Cancalon and Beidler, 1977;Weiss et al, 1978;1979;Black and Lasek, 1978). Both single and two-dimensional methods have indicated that these populations are very heterogeneous, and span a wide range of molecular weights and isoelectric points.…”
mentioning
confidence: 99%